Phase behavior and rheology of mixed nonionic sugar-based surfactants - Ismail, Zahariah; Kassim, Anuar; Suhaimi, Hamdan; Ahmad, Salmiah (Taylor and Francis Group, 2002)
The rheological properties of 40/60, 30/70, and 20/80 by weight ratio of methyl glucose sesquistearate (glucate SS) and PEG-20 methyl glucose sesquistearate (glucamate SSE-20) at 1-phase (Lα) and 2-phase (L1 + Lα) region were studied. These regions are fully developed lamellar liquid crystal (Lα) ranging from 29-31% water, lamella liquid crystal, and isotropic matrix which is closed Lα region (L1 + Lα) ranging from 16-19% water, and lamella liquid crystal in which birefringence is not prominent and isotropic matrix (L1 + Lα)′ ranging from 34-44% water. The viscosity, yield value and thixotropy behavior were studied at 80°C using a Brookfield viscometer. A pseudoplastic behavior exhibits at all the phases for mixed surfactants. The viscosity of mixed surfactants indicated as fall in the following order Lα> (L1 + Lα)′ > (L1 + Lα). The yield values of 40/60 and 20/80 exhibit the same ranking as the viscosity but not for 30/70. The highest plastic viscosity was observed in Lα region. The consistency index or viscosity index increased at Lα and it decreased in the flow index (flow index to describe the flow-curve, i.e., Newtonian, dilatant, pseudoplastic or plastic). The thixotropy behavior in that required a longer time to recover its structure of mixed surfactants showed at the Lα. Oily streaks pattern exhibits the biggest hysteresis loop.